Equality of Opportunities as a Non-Educational Concept - Blumsztajn, Anna (INSTED: Interdisciplinary Studies in Education & Society, 2019)
The paper reflects on the concept of equality of educational opportunities from the perspective of pedagogy, which is seldom used to analyze it. The main thesis of the paper assumes that the idea of equality of educational opportunities, so commonly used in educational policymaking, comes from a sociological background and therefore does not have a strictly educational content and meaning – which has conse-quences for the way it interacts with education. To develop this thesis, I will use a theoretical framework proposed by Piotr Zamojski. It is based on the classification of three phases or types of educational theories – technological-instrumental, critical and performative ones. Such approach allows to combine the ideological context with differences in the theoretical approach to educational research when analyzing the history of the concept of equal opportunities. The analysis shows that the concept is born in the technological-instrumental paradigm, and is still firmly rooted there, despite the shifts in its ideological content (from the egalitarian to the meritocratic). The concept of equal opportunities has helped “colonize” education, making it a major instrument of social policy from the 60’s onwards. But – as thinkers representing the critical perspective exposed – that tool was not, and could not have been a successful one in really changing the social structure. The paper finally gives voice to the third perspective, the performative one, which gives us hope for (re)filling the concept of equality of educational opportunities with educational meaning and sense, mainly through the propositions of Jacques Rancière.